2005
DOI: 10.1002/srin.200505992
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Sheet Metal Forming of Large Scale Structures from Sheets with Optimised Thickness Distribution

Abstract: In order to manufacture components optimised in regard to lightweight construction, the use of innovative forming processes like high‐pressure sheet metal forming (HBU) in combination with the use of tailor rolled blanks (TRB) as innovative semi‐finished materials is a promising solution. To realise a sufficient forming process reliability, at first, investigations on the seal system were carried out. Hereby, a non‐adjustable as well as a new adjustable seal system have been investigated and qualified as suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…The HFAsupply plate is integrated inside the press in front of the locking cylinder. The forming of a large-scale structure requires specific attention to the mechanical properties and the operating behaviour of the seal [25]. Simulation and optimisation.…”
Section: Investigations On the Large-scale Structurementioning
confidence: 59%
See 1 more Smart Citation
“…The HFAsupply plate is integrated inside the press in front of the locking cylinder. The forming of a large-scale structure requires specific attention to the mechanical properties and the operating behaviour of the seal [25]. Simulation and optimisation.…”
Section: Investigations On the Large-scale Structurementioning
confidence: 59%
“…The MSCs (cp. [23,24]) are positioned on both sides of the die [25]. The HFA-supply plate comprises six tactile flange draw-in sensors which measure the position of the flange edge during the forming operation.…”
Section: Investigations On the Large-scale Structurementioning
confidence: 99%
“…They concluded that through optimizing the sheet thickness distribution of TRB, the maximum draw depth could be increased and the weight could be reduced. Kleiner et al [ 6 ] successfully manufactured a large-scale component optimized in regard to lightweight construction by utilizing high-pressure sheet metal forming in combination with the use of TRB. Chatti and Kleiner [ 7 ] manufactured a front cross member with two thickness transition zones and two crash boxes.…”
Section: Introductionmentioning
confidence: 99%
“…Chatti and Kleiner [ 7 ] manufactured a front cross member with two thickness transition zones and two crash boxes. The work of Kleiner et al [ 6 ] and Chatti and Kleiner [ 7 ] showed the feasibility of the further formation of TRB into complex components in cooperation with reasonable processes.…”
Section: Introductionmentioning
confidence: 99%